Numbers : The Key To The Universe - Sage Angie
Is maths making you miserable? Are you scared of squares and perplexed by primes? Do numbers leave you...non-plussed? Then it's time to be utterly amazed, as you're whisked off to infinity and back with " The Key to the Universe". Find out how you could win a million dollars and become famous for ever (twice), discover the key to the evil Professor's Fiendish Number Chain, and travel to a distant planet for the biggest gig in all eternity. Meanwhile, things get ugly when the gangsterseet the unlucky number 13. This book contains no nasty exercises and no boring sums.